Pengaruh Kelompok Acuan, Kelas Sosial, dan Bauran Pemasaran Terhadap Keputusan Berbelanja Pada Swalayan Mitra Anda di Pontianak - Ricola Dewi Rawa; Melya Yosita; Puty Febriasari (Prodi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Panca Bhakti, 2022)
In almost all cities in Indonesia, there are shopping centers of various shapes and types. Malls, hypermarkets, supermarkets, minimarkets or supermarkets are easy to find in every corner of the city. Shopping places or shopping centers such as malls, hypermarkets, supermarkets, minimarkets or supermarkets that provide lots of daily necessities. This causes the competition for these retail companies to interact more tightly supported by very strong capital ownership in order to gain an advantage in entering a competitive market.The aims of this research are: (1) To find out the effect of the reference group on shopping decisions at your partner's supermarket in Pontianak. (2) To find out the effect of social class on shopping decisions at your partner's supermarket in Pontianak. (3) To find out the marketing mix on shopping decisions at your partner's supermarket in Pontianak. This research will be carried out from October 2021 to December 2021. The research method used is causal associative research while the method used in this associative research is a survey method. The data used in this research is cross sectional data. There are two sources of data used, namely, primary data and secondary data. Primary data was obtained from distributing questionnaires to consumers who shop at PT. Your partner Pontianak. Secondary data from this study such as data from the internet and newspapers. The regression method used is multiple linear regression method. The outputs generated from this research are: (1) able to provide information for practitioners in the field of marketing related to aspects that need to be considered in determining their target market. (2) The results of this research target will be included in an accredited journal (Jurnal Scientific Management, Mercu Buana University Jakarta, Sinta 2) which later this research can provide benefits to further researchers as reference material for conducting similar research. The results of the study show that many respondents shop at Mitra Anda Pontianak Supermarkets because there is a match between consumer expectations and desires. The researcher's suggestion is addressed to the Anda Mitra Supermarket Pontianak so that it further enhances the image of the Anda Mitra Supermarket Pontianak which is a public shopping place that does not limit incoming consumers, be it from the upper, middle or lower classes so that consumers if they want to shop at the Anda Mitra Supermarket Pontianak feel comfortable not influenced by the image that Mitra Anda Pontianak Supermarkets are only for the upper class. Researchers also provide suggestions. Maybe your Pontianak Partner Supermarkets make advertisements or billboards so that they can spread widely throughout the city of Pontianak.